The Impact of Work Culture and Attitudes on Job Satisfaction and Their Impact on The Performance of Mandau Regional General Hospital Employee - Alianti, Susi; Helwen Heri; Hadiyati; Agus Seswandi (Jurnal Manajemen dan Bisnis Terapan, 2023)
This study aims to determine the relationship between work culture and attitude on job satisfaction and performance of employees of Mandau Regional General Hospital, as well as their respective relationships. This study used a cross-sectional design with simple random sampling technique. Analysis and hypothesis testing using Structural Equation Modeling Partial Least Square (SEM-PLS). It can be concluded that work culture and attitudes are proven to have a significantly positive effect on job satisfaction (T statistic = 1.96). Culture and job satisfaction are not proven to significantly have a positive effect on employee performance (p value > 0.05). Job satisfaction is not proven to significantly have a mediating effect on performance and work culture as well. Future research is intended to include more hospitals and a larger sample size, allowing the analysis's findings to be more broadly generalized.